Nonlinear systems : analysis, stability, and control - Sastry, Shankar (Interdisciplinary applied mathematics ;, 2010)
"There has been a great deal of excitement over the last ten years concerning the emergence of new mathematical techniques for the analysis and control of nonlinear systems: witness the emergence of a set of simplified tools for the analysis of bifurcations, chaos, and other complicated dynamical behavior and the development of a comprehensive theory of geometric nonlinear control.